Population genetics of Thamnaconus hypargyreus (Tetraodontiformes: Monacanthidae) in the South China Sea. (3rd March 2016) - Li, Yufang; Chen, Guobao; Yu, Jie; Wu, Shuiqing; Xiong, Dan; Li, Xia; Cui, Ke; Li, Yongzhen
Abstract: Knowledge of population structure is particularly important for long-term fisheries management and conservation. Lesser-spotted leatherjacket Thamnaconus hypargyreus is an economically important fish species in the South China Sea. Fish specimens (totally 158 individuals) used in this study were collected from five geographical locations in the north of the South China Sea and the southwestern Nansha Islands. The results were as follows: a total of 636 nucleotides of the mitochondrial DNA (mtDNA) control region (CR) of T. hypargyreus were amplified by polymerase chain reaction (PCR) technology. Both 103 mutations of nucleotide acids without inserting or deleting one and 91 haplotypes were found among the examined CR fragment. High haplotype diversity (0.9419 ± 0.0151) and nucleotide diversity (0.0095 ± 0.00506) relatively together with a recent and sudden population expansion which characterizes the genetic population structure of this species. Analysis of molecular variance (AMOVA) and the fixation indices (Fst) of five groups showed that the genetic variance mainly came from individuals within groups, and there was no genetic differentiation between groups. The phylogenetic trees including maximum likelihood (ML) and Bayesian inference (BI) proved no phylogeographic differentiation structure in five groups. The mtDNA marker suggested the five groups should be genetic homogeneity, which implied T. hypargyreus in the north and southwest continental shelf of the South China Sea belongs to one population.